2007
DOI: 10.1590/s0100-40422007000200018
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que governam a especiação do cobre em ambientes aquáticos urbanos: evidências da contribuição de sulfetos solúveis

Abstract: Recebido em 3/1/06; aceito em 23/6/06; publicado na web em 19/1/07 FACTORS GOVERNING COPPER SPECIATION IN URBAN FRESHWATERS: EVIDENCES ON THE CONTRIBUTION OF SOLUBLE SULFIDES. Copper speciation and behavior in different rivers located in the city of Curitiba were evaluated in this work. Sampling locations were selected to cover different levels of urbanization regarding their anthropogenic occupation and land use. Results showed that in highly-developed areas, both organic matter and dissolved sulfides were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(64 reference statements)
0
3
0
8
Order By: Relevance
“…The Barigui River, Carvalho et al [69] (2013) presented total alkalinity values ranging from 156.8 to 212.8 mg x L -1 CaCO 3 . In the study by Scheffer [70] found 133 mg x L -1 CaCO 3 for the same environment. It should be noted that Fritzsons [71] states that the alkalinity in most Brazilian rivers is between 30 and 500 mg x L -1 CaCO 3 .…”
Section: Determination Of Total Alkalinity Nutrients and Chlorophyllmentioning
confidence: 88%
“…The Barigui River, Carvalho et al [69] (2013) presented total alkalinity values ranging from 156.8 to 212.8 mg x L -1 CaCO 3 . In the study by Scheffer [70] found 133 mg x L -1 CaCO 3 for the same environment. It should be noted that Fritzsons [71] states that the alkalinity in most Brazilian rivers is between 30 and 500 mg x L -1 CaCO 3 .…”
Section: Determination Of Total Alkalinity Nutrients and Chlorophyllmentioning
confidence: 88%
“…Thus, in aquatic systems with acidic pH, this metal is usually dissolved in water (Milesi, Biasi, Restello, & Hepp, 2008). However, at a pH of about 8, Cu is mostly precipitated in the form of copper hydroxide or in stable complexes with sulfides, which exert oxidative effects and dissociation (Scheffer, Sodré, & Grassi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2. Statistical results of the concentrations of metals in the water samples collected from the drainage basin studied Studies on the adsorption of copper to organic matter in drainage basins have demonstrated that the pH value and amount of particulate organic matter alter the distribution of copper in the water column (Scheffer et al, 2007). The mean copper concentration in the water of the drainage basin studied was higher than the median value, indicating asymmetrical distribution.…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 94%